Combining polyesters of citric and azelaic acids to obtain potential topical application biomaterials with antimicrobial activity - Aleksandra Bandzerewicz; Anna Herman; Ewa Dutkowska; Klara Niebuda; Paweł Ruśkowski; Agnieszka Gadomska-Gajadhur (Frontiers in Bioengineering and Biotechnology)
Biomaterials with antimicrobial properties are a key research area due to the increasing threat of infections and the growing resistance of microorganisms to existing antibiotics. The aim of the study was to produce thermally cross-linked polymer films based on poly(1,5-pentanediol azelate) and poly(1,4-butanediol citrate) with antimicrobial activity for medical applications. Well-formed, cross-linked, flexible materials differing in appearance depending on the conditions of the cross-linking process were obtained. In general, a lower cross-linking temperature was found to promote less brittle and more flexible films with greater structure uniformity. The polymer films had hydrophilic surfaces (water contact angle 40°–60°). All polymer films maintained integrity after immersion in PBS buffer. Most likely, the lower hydrophilicity of the polyazelate phase limited their degradation. A modified time-kill procedure (ASTM E2315-23) was performed to test the antimicrobial properties of the films against Pseudomonas aeruginosa, Staphylococcus aureus, and Candida albicans. The antimicrobial activity of polycitrate-based films against P. aeruginosa has been reported with >90% reduction of the pathogen after 6 h of contact and 100% biocidal effect after 24 h. The antimicrobial activity of the film is pH-based. The biocidal effect of polycitrate film against P. aeruginosa is the most important and promising result, especially given the resistance of the pathogen to commonly used antibiotics.